PTH-046 Benchmarking Endoscopy Services In Iraq – Results Of A National Survey. (9th June 2014) - Hawkes, N; Al-Rubaiy, L; Hawkes, B; Aziz, M
Abstract : Introduction: In the UK the Global Rating Scale (GRS) has been adopted as QA tool to improve the standards of endoscopic practice and of the patient experience. Endoscopy in Iraq is provided by a number of training and regional centres but without the level of integration seen in the NHS. We sought to benchmark practice against UK quality standards by surveying the main training centres and service providers of endoscopy in Iraq. Methods: A Survey Monkey questionnaire with 40 questions relating to local endoscopic practice and based on defined areas of the GRS was sent to departmental leads in all regional centres in Iraq performing GI endoscopy by the President of the Iraqi Medical Society International. 24/35 responses (69%) were received (all 12 major institutions responded). Results: 67% of respondents were from University Teaching Hospitals, others worked in Regional Public or Private Hospitals. Population served ranged from 100, 000 to 10 million; reflected in lists performed per week (range 3 to 20+). All Units perform diagnostic upper and lower GI endoscopy. Whilst 90% perform some ERCP, only half perform >250 per year. Figures for EUS were similar (85% some EUS, 55% >250 cases per year). Enteroscopy is only performed in small numbers. No agreed performance standards exist on a national level. Access to modern endoscopes, accessories and diathermy was acceptable. Survey data aligned to the patient experience, quality of procedure, workforce and training highlighted resource and training gaps: only 70% of respondents use a structured referral form with stratification of urgent cases, 54% are able to vet appropriateness of referral and 20% can effectively audit referral practice. Written information about procedures is limited and the practice of informed consent falls short of UK standards. Numbers of recovery beds and staffing levels varied widely. Patient monitoring equipment was not universally available. 47% have an ERS, 47% paper-based records and 16% no reporting system. Morbidity and mortality, sedation practice and patient experience were recorded in less than half of responding institutions. Centres with a large numbers of trainees tend to have experienced trainers but assessment tools and training goals varied across institutions. Data on workforce was inconsistent, with conflicting reports from respondents working in the same institution. Conclusion: Web-based surveys provide a means of investigating and benchmarking endoscopic practice, via non-UK national societies, against the quality standards integral to the GRS. Resource and training gaps have been identified using this method and will inform a planned BSG sponsored visit to Iraq to deliver targeted training on quality assurance, safety and training for endoscopy. Disclosure of Interest: None Declared.